2004
DOI: 10.1021/jp048389q
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation Conditions of Methane Hydrate in Mesoporous Silica Gels in Wide Ranges of Pressure and Water Content

Abstract: The temperature of methane hydrate dissociation in silica mesopores has been monitored within a wide range of pressures from 10 MPa to 1 GPa. Because the determination of pore size appears to be crucial for the studied phenomenon, several methods of calculation have been applied. According to our findings, the size that corresponds to the mean size of the most representative pores is to be considered as the most reliable. It was concluded that the shape of hydrate particles replicates a host space of pores and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…Theoretical studies indicate that the gas-liquid capillary pressure has an opposite effect on the methane hydrate phase boundary as it inhibits the formation of gas bubbles and thus makes methane hydrate more stable in pores (Buffett & Zatsepina, 1999;Henry et al, 1999;Liu & Flemings, 2011;Yagasaki et al, 2014). The net effect of gas-liquid and hydrate-liquid capillary pressure is to shift the methane hydrate phase boundary toward higher temperature/lower pressure (Liu & Flemings, 2011), which was observed by Aladko et al (2004) in pores with radius less than 5 nm. However, experiments that include both the gasliquid and hydrate-liquid capillary pressure are rare in literatures.…”
Section: Influence Of Salinity and Capillary Pressure On The Methane mentioning
confidence: 99%
“…Theoretical studies indicate that the gas-liquid capillary pressure has an opposite effect on the methane hydrate phase boundary as it inhibits the formation of gas bubbles and thus makes methane hydrate more stable in pores (Buffett & Zatsepina, 1999;Henry et al, 1999;Liu & Flemings, 2011;Yagasaki et al, 2014). The net effect of gas-liquid and hydrate-liquid capillary pressure is to shift the methane hydrate phase boundary toward higher temperature/lower pressure (Liu & Flemings, 2011), which was observed by Aladko et al (2004) in pores with radius less than 5 nm. However, experiments that include both the gasliquid and hydrate-liquid capillary pressure are rare in literatures.…”
Section: Influence Of Salinity and Capillary Pressure On The Methane mentioning
confidence: 99%
“…3). Earlier studies also showed that silica particles exhibit thermodynamic inhibition during methane and natural gas hydrate formation [18,19].…”
Section: Methodsmentioning
confidence: 99%
“…Evidence shows that the pore sizes (Ruppel, 1997;Clennell et al, 1999), surface structure and mineral composition of the medium may influence the three-phase equilibrium conditions of gas hydrate. Recent workers have done many experiments to determine the three-phase equilibrium conditions of gas hydrate in porous medium (Handa and Stupin, 1992;Uchida et al, 1999Uchida et al, , 2002Seshadri et al, 2001;Seo et al, 2002;Smith et al, 2002a,b;Zhang et al, 2002;Seo and Lee, 2003;Anderson et al, 2003b;Aladko et al, 2004). These studies indicate that the capillary force can inhibit the formation of gas hydrate in small pores.…”
Section: Influence Of Porous Mediummentioning
confidence: 99%